Azide-Alkyne Cycloaddition Catalyzed by a Glucose/Benedict Reagent System - Jesús G. García Torres; Andrés F. Becerra-Buitrago; Luis Carlos García-Sánchez; Marco A. García-Eleno; M. V. Basavanag Unnamatla; Erick Cuevas-Yañez (Chemistry Proceedings, 2021)
Benedict’s Reagent is commonly used in identifying reducing sugars through a redox process where a Cu(I) species is generated. Despite the simplicity of this reaction, this has barely been investigated as a copper (I) source for catalytic processes. In this report, diverse organic azides and alkynes were reacted in the presence of catalytic amounts of a Glucose–Benedict Reagent system, obtaining the corresponding 1,2,3-triazoles through a simple and environmentally friendly synthetic procedure.